Quality Assurance and Control of Indonesian Wooden Ship - Ucok, Zulkairnain; Junaidi, Abd Khair (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
Demand for traditional ship in Indonesia is very high, because the ship is used of fishermen for catching fish as a livelihood. Shipbuilders as manufactures play an important element in building safety and good traditional wooden ships. In the production process, the shipbuilders must be has proper quality control system, in order to match with the owner specification, regulation, and statutory. Therefore, this article discusses about quality control system in traditional ship production process. The research were conducted by direct survey to traditional shipbuilders in Kepulauan Riau-Indonesia by inspect some ships by visual eyes only. From the survey, it was found many discrepancies occur, such as the use of wood has many defects, knur, knot and cracks. In addition, the wood concatenation process is not perfect, which can cause leakage. From the study, the shipbuilders should conduct quality control using other tools instead of visual technique only.